EFFECT OF HEALTH EDUCATION ABOUT THE DANGERS OF E-CIGARETTES ON E-CIGARETTE CONSUMPTION BEHAVIOR IN YOUTH SMK "X" TANGERANG - Nurry Ayuningtyas Kusumastuti; Eva Marsepa; Anjani Anjani (Jurnal Delima Harapan, 2023)
Background: Cigarettes are one of the biggest threats to the development of a country. Indonesia is the 3rd largest smoker in the world after China and India. CHT rates do not contribute significantly to the decline in the level of smokers in Indonesia because they change over to e-cigarettes. Objective: The purpose of this study was to determine the effect of health education on the dangers of e-cigarettes on the behavior of e-cigarette consumption among adolescents at SMKN Tangerang. Methods: This study used a quasi-experimental research with a pretest – posttest two group design. The population in this study were all male students of SMKN Tangerang with simple random sampling technique. The number of samples was 30 students who were divided into 15 respondents in the intervention group and 15 respondents in the control group. The data using a questionnaire. Data analysis using Mann-Whitney test. Results: This study showed p -value = 0.015 (p <0.05), the mean ± SD in the intervention group was 1.00 ± 0.93 and non-intervention group 1.00 ± 0.53. Conclusion: there was effect of health education with e-cigarette consumption behavior in adolescents at SMKN X Tangerang.